Framing The Sundanese Gastronomic Tourism Experience in a Pop-Up Restaurant - Ainurrohmah, Syifa; Ismarizal, Beni; Turgarini, Dewi; Ningsih, Caria (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this study was to find out how the consumer experience at pop events in the city of Bandung enjoys Sundanese gastronomic tourism. The data from this study consisted of 22 informants, using qualitative methods. The results of this study found two findings, namely (1) Sundanese gastronomic tourism as a tourist attraction in sustainable tourism (2) Sundanese gastronomic tourism in pop up events as the development of innovative local food products. The implication of this research in the field of tourism is that it can become a gastronomic tourism business development.